2015
DOI: 10.1016/j.surg.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Green tea component epigallocatechin-3-gallate decreases expression of osteopontin via a decrease in mRNA half-life in cell lines of metastatic hepatocellular carcinoma

Abstract: Introduction Osteopontin (OPN) mediates metastasis and invasion of hepatocellular carcinoma (HCC). Epigallocatechin-3-gallate (EGCG), found in green tea, suppresses HCC tumor growth in vitro. We sought to investigate the role of EGCG in modulating OPN in cell lines of metastatic HCC. Methods Experimental HCC cell lines included HepG2 and MHCC-97H HCC cells, which express high levels of OPN, and the Hep3B cells, which express lesser levels of OPN. Cells were treated with EGCG (0.02–20 μg/mL) before measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
(35 reference statements)
0
12
0
Order By: Relevance
“…Our cell migration assay demonstrated that miR-221 is necessary for EGCG-induced delay in wound closure, and miR-221 can mimic the effects of EGCG. Previous work from our lab has demonstrated that EGCG treatment at these concentrations does not affect cell viability [25], and therefore should have minimal consequences on wound closure. Alamar Blue bioassay also demonstrated that miR-221 modulation does not affect cell viability when concomitantly treated with TAA with or without EGCG (S1 Fig).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our cell migration assay demonstrated that miR-221 is necessary for EGCG-induced delay in wound closure, and miR-221 can mimic the effects of EGCG. Previous work from our lab has demonstrated that EGCG treatment at these concentrations does not affect cell viability [25], and therefore should have minimal consequences on wound closure. Alamar Blue bioassay also demonstrated that miR-221 modulation does not affect cell viability when concomitantly treated with TAA with or without EGCG (S1 Fig).…”
Section: Discussionmentioning
confidence: 99%
“…EGCG-mediated OPN mRNA degradation leads to decreased wound closure [25]. However, the mechanism and the effects of EGCG on OPN in vivo have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, EGCG is able to diminish tumor angiogenesis and stall growth [ 72 ]. In addition, there is strong evidence that EGCG is capable of diminishing migration and metastasis formation of tumors [ 73 , 74 ]. Previous studies report that EGCG promotes a reduction in the migration and metastasis formation of tumor cells with tumor size reduction, accomplishing a more reliable and efficient chemotherapy [ 75 77 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the catechins EGCG downregulates OPN expression by reducing the half-life of EGCG mRNA, EGCG-mediated mRNA degradation leads to reduced closure of wounds (Zapf et al 2015).…”
Section: Introductionmentioning
confidence: 99%